Identification of novel neutralizing single-chain antibodies against vascular endothelial growth factor receptor 2 - (:unkn) unknown (WILEY, 2011)
Human vascular endothelial growth factor (VEGF) and its receptor (VEGFR-2/kinase domain receptor [KDR]) play a crucial role in angiogenesis, which makes the VEGFR-2 signaling pathway a major target for therapeutic applications. In this study, a single-chain antibody phage display library was constructed from spleen cells of mice immunized with recombinant human soluble extracellular VEGFR-2/KDR consisting of all seven extracellular domains (sKDR D17) to obtain antibodies that block VEGF binding to VEGFR-2. Two specific single-chain antibodies (KDR1.3 and KDR2.6) that recognized human VEGFR-2 were selected; diversity analysis of the clones was performed by BstNI fingerprinting and nucleotide sequencing. The single-chain variable fragments (scFvs) were expressed in soluble form and specificity of interactions between affinity purified scFvs and VEGFR-2 was confirmed by ELISA. Binding of the recombinant antibodies for VEGFR-2 receptors was investigated by surface plasmon resonance spectroscopy. In vitro cell culture assays showed that KDR1.3 and KDR2.6 scFvs significantly suppressed the mitogenic response of human umbilical vein endothelial cells to recombinant human VEGF165 in a dose-dependent manner, and reduced VEGF-dependent cell proliferation by 60% and 40%, respectively. In vivo analysis of these recombinant antibodies in a rat cornea angiogenesis model revealed that both antibodies suppressed the development of new corneal vessels (p < 0.05). Overall, in vitro and in vivo results disclose strong interactions of KDR1.3 and KDR2.6 scFvs with VEGFR-2. These findings indicate that KDR1.3 and KDR2.6 scFvs are promising antiangiogenic therapeutic agents.
Keywords: antiangiogenic; corneal angiogenesis assay; HUVEC; phage display; single-chain variable fragment (scFv); vascular endothelial growth factor receptor-2 (VEGFR-2); ANTI-VEGF THERAPY; MONOCLONAL-ANTIBODY; IN-VIVO; ARTERIOVENOUS-MALFORMATIONS; ANGIOGENESIS; BEVACIZUMAB; INHIBITION; CANCER; EXPRESSION; CELLS